(3GdeONd dOQGSI GdYdhe GdbGfhfjI (B:s (3eHGOF GdbGfhf, GdfXQjI GdYGeI ddMb (B= Introduction to the legal sciences study : principles of law, general theory of the right /s - (3GdaGQ, YHO GdbGOQs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2019)
(3jgJe gPG GdcJGH HOQGSI eHGOF GdbGfhf ajHOC aj GdHGH GdJegjOj HJYQja GdbGfhf HCfg eLehYI GdbhGYO GdJj JMce Ch JfXe Sdhc GdCaQGO aj GdeLJeY hGdJj jLHQ GdCaQGO Ydi GJHGYgG HGdbhI YfO GdGbJVGA, hhXjaI GdbGfhf OYe GdSdGe aj GdeLJeY hGdJhajb Hjf GdeUGdM GdeJYGQVI aj GdeLJeY hJMbjb GdYOd Ke, jPcQ eQGMd fTCI GdbGfhf aj YgO GdbhI hYgO GdJbGdjO GdOjfjI hYUQ GdJOhjf hGdYUQ GdMOjK, hjTjQ Edi GdePGgH GdeNJdaI aj CUd GdbGfhf hgj GdeKGdjI hGdhVYjI hePgH GdJWhQ GdJGQjNj hGdePGgH GdeNJdaI, haj GdHGH GdChd jJfGhd GdbGYOI GdbGfhfjI hNUGFUgG, haj GdHGH GdKGfj jbSe GdcJGH GdbGfhf Edi bGfhf YGe hNGU EPG cGf GdfXQ Edi ehVhY hCTNGU GdYdGbGJ GdJj jfXegG GdbGfhf hjecf JbSje GdbhGYO GdbGfhfjI ef MjK bhI EdRGegG Edi bhGYO BeQI hbhGYO ecedI eaSQI hef fGMjI KGdKI jecf JbSje GdbhGYO GdbGfhfjI Edi bhGYO ehVhYjI hbhGYO ELQGFjI aGdbhGYO GdehVhYjI gj GdJj JVY JfXjeG ehVhYjG ddYdGbGJ GdbGfhfjI agj JHjf GdMbhb hGdhGLHGJ CeG bhGYO GdELQGFjI agj JHjf GdChVGY hGdELQGAGJ GdJj jLH GJHGYgG ddhUhd Edi GMJQGe GdbhGYO GdehVhYjI, hjJfGhd aj GdHGH GdKGdK GdeUGOQ GdQSejI ddbGfhf GdCQOfj hgj GdJTQjY hCMcGe Gdabg GdESdGej hGdYQa hbhGYO GdYOGdI hCeG GdeUGOQ ZjQ QSejI (B"(3GdGSJFfGSjI(B" (3agj GdbVGA hGdabg GdCQOfj efgG hGdYQHj(B.s
(3HHdjhLQGajI (B: (3UaMI (B239-240. s
Keywords: (3GdbGfhfs -- (3adSaIs; (3GdHMhK GdbGfhfjIs; (3fXQjI GdMbs